Segmented Work Divided Workers : The Historical Transformation of Labour in the United States - White, Jerry P. (Relations Industrielles / Industrial Relations, 1985)
This article reviews the book, "Segmented Work Divided Workers : The Historical Transformation of Labour in the United States," by David Gordon, Richard Edwards & Michael Reich.